2007
DOI: 10.1177/0960327107071918
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for PCR-SSCP among the methods for missense mutation detection of TP53 gene?

Abstract: Mutation analysis methods have increased in variety during the past years. High-throughput microarray methods have especially increased in popularity. However, new methods require reference points, and not all of the methods are equal in sensitivity and specificity. Furthermore, the detection of unknown missense mutations, such as unknown TP53 mutations in human tumors, for clinical purposes requires great accuracy, which may be difficult to acquire with the current high-throughput methods. For these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Therefore, the mutations in the P53 gene have a great impact on cancer development and maybe a clinically useful predictor of prognosis in mammals (Nakamori et al, 1995). The analysis by single-strand conformation polymorphism (SSCP) method allows the detection of different types of mutations such as base substitutions, small insertions, deletions, and rearrangements (Peltonen, Welsh, and Vahakangas 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mutations in the P53 gene have a great impact on cancer development and maybe a clinically useful predictor of prognosis in mammals (Nakamori et al, 1995). The analysis by single-strand conformation polymorphism (SSCP) method allows the detection of different types of mutations such as base substitutions, small insertions, deletions, and rearrangements (Peltonen, Welsh, and Vahakangas 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Two different temperatures (4°C and 20°C) were used to obtain good efficiency. Several studies have shown that the optimization of SSCP conditions is essential for analytical sensitivity and efficiency (for review see) [26]. Both negative and positive controls were included in each run to ensure the quality of the run.…”
Section: Methodsmentioning
confidence: 99%